Democratic Republic of Sao Tome and Principe : Staff Report for the 2011 Article IV Consultation.. (IMF Staff Country Reports; Country Report ;, 2012)
Sao Tome and Principe remains at high risk of debt distress, although it has received substantial debt relief. The increases in world food and fuel prices have rekindled domestic inflation pressures. Inflation has declined substantially since 2008, but remains at double-digit levels. A tightening of fiscal and monetary policies in 2008 followed by a decline in world food and oil prices helped lower year-over-year inflation from a peak of 37 percent in July 2008 to 11.5 percent in June 2010.